Fostering Innovation of Thinking for Student-Facing Mathematics Difficulty Through Commercial Sport Video Games - Herfa Maulina Dewi Soewardini; Hery Setiyawan; Dwi Juniati; Siti Khabibah; Abdul Talib bin Bon (NAROTAMA UNIVERSITY, 2020)
Every student likes a game that can keep him entertained by the many lessons at school. When they find it difficult to understand mathematical concepts in class, they tend not to show innovation in thinking when completing practice questions. Students mostly access video games via smartphones to forget learning difficulties. Furthermore, designed digital audio media related to sports and that obtained by students, namely commercial sports video games. From the results of the study, it turns out students who play commercial sports video games show innovative thinking skills, more comfortable to learn concepts, and enjoy mathematics. They can interpret according to what is in the scheme and written using a mathematical model.